Survey of management practices related to parasite control from ranched North American bison (Bison bison) in the southern United States - Kaylee R. Kipp; Joe L. Luksovsky; Christine M. Budke; Walter E. Cook; John S. Gilleard; Guilherme G. Verocai (Veterinary Parasitology, 2026)

A climate services organization supporting coastal resilience: lessons from the Stone Living Lab - K. A. Dafforn; M. Borrelli; K. Bosma; J. E. K. Byrnes; L. Castro-Diaz; R. F. Chen; J. Christo; D. Cook; F. Peri; R. Shoer; M. Albert; K. Bradley; et al. (Climatic Change, 2026)
There is a growing recognition that effective climate adaptation requires organizations that can translate science into policy-relevant, place-based implementation. The Stone Living Lab (SLL) was established as a climate services organization to help bridge the gap between climate adaptation research and real-world application. In this paper, we present the Lab as a model for how universities and NGOs can partner with government agencies, Indigenous groups, and local communities to strengthen coastal resilience, highlighting the structures, guiding principles and lessons learned over the last five years. Four guiding principles shape and distinguish the Lab’s approach, extending beyond the traditional focus on science and engineering research to also include climate preparedness, education and outreach and policy engagement. These principles continue to evolve in response to experience, particularly in navigating complex partnerships and engaging with stakeholder networks, which require sustained coordination, clear communication, and intentional alignment of roles, expectations, and timelines. Other lessons highlight the importance of visible, place-based solutions, knowledge sharing and maintaining a clear mission focus while balancing short-term outcomes with long-term resilience goals. Our aim here is to provide practical insights for researchers, practitioners and managers seeking to design or strengthen similar climate services organizations.

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

A systems modelling approach to predict biological responses to extreme heat - Daniel W.A. Noble; Margaret M. Mayfield; Ary A. Hoffmann; Zhong-Hua Chen; Steven J. Lade; Xuemei Bai; Danielle A. Way; Belinda E. Medlyn; Owen K. Atkin; Adrienne B. Nicotra; James M. Cook; Brajesh K. Singh; et al. (Trends in Ecology & Evolution, 2026)

Longitudinal patterns of urinary biomarkers of placental and renal function in pregnancy and associations with early pregnancy exposure to phthalates and replacements - Erin E. McNell; Danielle R. Stevens; Barrett M. Welch; Suzanne Fenton; Antonia M. Calafat; Julianne Cook Botelho; Elena Sinkovskaya; Ann Przybylska; George Saade; Alfred Abuhamad; Kelly K. Ferguson (Reproductive Toxicology, 2026)

American oak imports to Britain and Ireland in the 18th and early 19th centuries; The dendrochronological evidence - A. Crone; A. Arnold; R. Bale; M. Bridge; D. Brown; E. Cook; C. Griggs; R. Howard; D. Miles; C. Mills; N. Nayling; C. Tyers; et al. (Dendrochronologia, 2026)

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Collaborative evaluation of in silico predictions for high throughput toxicokinetics - John F. Wambaugh; Nisha S. Sipes; Gilberto Padilla Mercado; Jon A. Arnot; Linda Bertato; Trevor N. Brown; Nicola Chirico; Christopher Cook; Daniel E. Dawson; Sarah E. Davidson-Fritz; Stephen S. Ferguson; Michael-Rock Goldsmith; et al. (Toxicology in Vitro, 2026)

Adding value to imperfect long-term animal monitoring data for conservation insight - S.D. Sarre; E.J. Stringer; R. Brawata; E. Carlson; R. Colley; E. Cook; B. Croak; L.I. Doucette; M. Hoehn; B. Howland; W.S. Osborne; S. Pulsford; et al. (Biological Conservation, 2026)

Exploring Marine Mammal Cognition as a Conservation Tool - Gordon B. Bauer; Peter F. Cook; Heidi E. Harley; Jason Bruck; Mel Cosentino; Charles J. Deutsch; Nicola Erdsack; Wendi Fellner; Tabitha Gunnars; Heather Manitzas Hill; Sonia V. Kumar; Malin K. Lilley; et al. (Marine Mammal Science, 2026)
Cognition is an animal's real‐time adaptation system for responding to change. Rapid environmental change, often anthropogenic, is expanding the range and severity of challenges confronting wild animals. Effective conservation requires a multifaceted approach that includes animals' capacities. Large‐brained, long‐lived animals such as marine mammals often have extensive capability to adaptively modify their behavior due to their cognition, which comprises the mechanisms of information acquisition, processing, and flexible action. Consequently, current behavior need not be a final predictor of future behavior for these animals. This flexibility provides an underutilized and under examined point of leverage for humans interested in improving life outcomes for wild animals. In this team‐written, interdisciplinary paper, we argue that application of cognitive approaches may facilitate many conservation efforts directed toward marine mammals. Starting with a workshop on this topic at the 24th Biennial Conference on the Biology of Marine Mammals, scientists representing a wide range of disciplinary expertise addressed eight different conservation concerns for six marine mammal species and provided potential cognitive explanations of and interventions aimed at related behavior. Our treatment highlights the value of integrated laboratory and field research, and the importance of tight lines of communication between scientists and conservation managers.

The Properties of Individual Fire Events Are Essential for Understanding Global Fire Regimes - Adam L. Mahood; Ty Tuff; Megan E. Cattau; Virginia Iglesias; Thomas E. Hanson; Jilmarie Stephens; Nayani Ilangakoon; Maxwell C. Cook; R. Chelsea Nagy; David Barnard; E. Natasha Stavros; Amy DeCastro; et al. (Global Ecology and Biogeography, 2025)
Aim As fire activity changes globally, we need to better understand the spatial and temporal characteristics of the individual events that, when aggregated, constitute fire regimes. Most global studies analyze point detections of burned area, without delineating or considering the properties of individual events. Furthermore, there is a critical need to understand fire patterns within the context of the geopolitical boundaries within which fires are managed. Location Global. Time Period 2003–2020. Major Taxa Studied Fire. Methods We divided 241 countries by Köppen‐Geiger climate classifications and quantified four event‐based fire regime metrics: size, duration, and mean and maximum growth rate; and four area‐based metrics: burned area, number of fires, season length, and season peak. We examined the correlations among fire regime components, and between each fire regime component and climate normals. We quantified temporal trends, and used mixed models to analyze how climate and landcover change were associated with event‐based components of fire regimes. Results Event‐based metrics were weakly correlated with area‐based metrics. Countries with warmer and less variable climates had high burned area, more fire events, longer season lengths and shorter event durations. Countries with high annual temperature range and low precipitation tended to have fewer events but larger fires that were faster‐spreading and occurred later in the year. The growth rate and size of individual fire events are increasing in 18% and 21% of regions we analysed, respectively. Interannual variability in size and growth rate was associated with aridity increases in boreal areas, and landcover changes in arid areas. Main Conclusions Drivers of burned area and fire seasonality are well understood but largely unrelated to the properties of individual events. A more detailed understanding of the spatial and temporal aspects of fire events at broad scales will assist fire management efforts in preparing for a warmer future.

Characteristics of aqueous film forming foam (AFFF) sites impacted with per- and polyfluoroalkyl substances (PFAS): A 37-site study - Poonam R. Kulkarni; Nicolette E. Andrzejczyk; Arun Gavaskar; Abigail Cartwright; David T. Adamson; John Cook; Charles J. Newell (Water Research, 2025)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Ecosystem-wide PFAS characterization and environmental behavior at a heavily contaminated desert oasis in the southwestern U.S. - Jean-Luc E. Cartron; Chauncey R. Gadek; Jonathan L. Dunnum; Christopher C. Witt; Mariel L. Campbell; Samuel J. Romero; Andrew B. Johnson; Julie Kutz; Christopher Wolf; Sarah J. Choyke; Joseph A. Cook (Environmental Research, 2025)

Exposure to phthalates and replacements during pregnancy in association with gestational blood pressure and hypertensive disorders of pregnancy - Erin E. McNell; Danielle R. Stevens; Barrett M. Welch; Emma M. Rosen; Suzanne Fenton; Antonia M. Calafat; Julianne Cook Botelho; Elena Sinkovskaya; Ann Przybylska; George Saade; Alfred Abuhamad; Kelly K. Ferguson (Environmental Research, 2025)

Varying climate signals embedded in latewood blue intensity along an elevational gradient: A multi-species case study from the Great Basin, Nevada, USA - Karen E. King; Edward R. Cook; Paul J. Krusic; Daniel J. King (Dendrochronologia, 2025)

Prenatal per- and polyfluoroalkyl substance mixtures and weight for length from birth to 12 months: The New Hampshire Birth Cohort Study - Gyeyoon Yim; Caitlin G. Howe; Lisa G. Gallagher; Diane Gilbert-Diamond; Antonia M. Calafat; Julianne Cook Botelho; Margaret R. Karagas; Megan E. Romano (Science of The Total Environment, 2025)

Prenatal per- and polyfluoroalkyl substances and blood pressure trajectories in the New Hampshire Birth Cohort Study - Yuting Wang; Elizabeth C. Anderson; Caitlin G. Howe; Jiang Gui; Lisa G. Gallagher; Brianna Heggeseth; Julianne Cook Botelho; Antonia M. Calafat; Margaret R. Karagas; Megan E. Romano (International Journal of Hygiene and Environmental Health, 2025)

Cross-cultural evidence that intergroup conflict heightens preferences for dominant leaders: A 25-country study - Lasse Laustsen; Xiaotian Sheng; M. Ghufran Ahmad; Laith Al-Shawaf; Benjamin Banai; Irena Pavela Banai; Michael Barlev; Nicolas Bastardoz; Alexander Bor; Joey T. Cheng; Anna Chmielińska; Alexandra Cook; et al. (Evolution and Human Behavior, 2025)

Ecosystem Services Provided by Seaweed Cultivation: State of the Art, Knowledge Gaps, Constraints and Future Needs for Achieving Maximum Potential in Europe - Fricke A; Capuzzo E; Bermejo R; Hofmann LC; Hernández I; Pereira R; Van den Burg SWK; Pereira T; Buschmann AH; Cottier-Cook EJ (Reviews in Fisheries Science & Aquaculture, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Remotely Sensed Fire Heterogeneity and Biomass Recovery Predicts Empirical Biodiversity Responses - Rebecca K. Gibson; Don A. Driscoll; Kristina J. Macdonald; Grant J. Williamson; Rachael H. Nolan; Tim S. Doherty; Dale G. Nimmo; Euan G. Ritchie; Mark Tozer; Liz Tasker; Aaron Greenville; Adam Roff; et al. (Global Ecology and Biogeography, 2025)
Aim To compare field‐based evidence of plant and animal responses to fire with remotely sensed signals of fire heterogeneity and post‐fire biomass recovery. Location South‐eastern Australia; New South Wales. Time Period 2019–2022. Major Taxa Studied A total of 982 species of plants and animals, in eight taxonomic groups: amphibians, birds, fish, insects, mammals, molluscs, plants and reptiles. Methods We collated 545,223 plant and animal response records from 47 field surveys of 4613 sites that focussed on areas burnt in 2019–2020. For each site, we calculated remotely sensed signals of fire heterogeneity and post‐fire biomass recovery, including the delayed recovery index. Meta‐regression analyses were conducted separately for species that declined after fire (negative effect sizes) and species that increased after fire (positive effect sizes) for each buffer size (250 m, 500 m, 1 km, 1.5 km, 2 km and 2.5 km radius). Results We found that species exposed to homogenous high‐severity fire (i.e., low fire heterogeneity) were more likely to exhibit decreased abundance/occurrence or inhibited recovery. Areas with delayed recovery of biomass also had significant negative on‐ground responses, with lower abundance or occurrence in areas where biomass recovery was slower. Main Conclusions The fire heterogeneity index and the delayed recovery index are suitable for inclusion in monitoring and reporting systems for tracking relative measures over time, particularly when field survey data is not available at the landscape scales required to support reporting and management decisions. Locations with remotely sensed signals of delayed recovery should be prioritised for protection against further disturbances that may interfere with the recovery process. Research attention must next focus on how cumulative fire heterogeneity patterns of successive fires affect the post‐fire recovery dynamics to further inform the application of remote sensing indicators as management tools for biodiversity conservation.

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

A new certified reference material IAEA-465 for radionuclides in Baltic Sea sediment - M.K. Pham; M.-O. Aust; J. Bartocci; O. Blinova; F.P. Carvalho; E. Chamizo; M. Cook; D. Degering; M. Fujak; C. Gascó; R. Gurriaran; V. Jobbágy; et al. (Journal of Environmental Radioactivity, 2024)

A 561-yr (1461-2022 CE) summer temperature reconstruction for Mid-Atlantic-Northeast USA shows connections to volcanic forcing and atmospheric circulation - Grant L. Harley; Justin T. Maxwell; Karen E. King; Shelly A. Rayback; Edward R. Cook; Christopher Hansen; R. Stockton Maxwell; Frederick Reinig; Jan Esper; Tsun Fung Au; Ellen V. Bergan; Katherine E. Brings; et al. (Climatic Change, 2024)
Contextualizing current increases in Northern Hemisphere temperatures is precluded by the short instrumental record of the past ca. 120 years and the dearth of temperature-sensitive proxy records, particularly at lower latitudes south of <50 °N. We develop a network of 29 blue intensity chronologies derived from tree rings of Tsuga canadensis (L.) Carrière and Picea rubens Sarg. trees distributed across the Mid-Atlantic and Northeast USA (MANE)—a region underrepresented by multi-centennial temperature records. We use this network to reconstruct mean March-September air temperatures back to 1461 CE based on a model that explains 62% of the instrumental temperature variance from 1901−1976 CE. Since 1998 CE, MANE summer temperatures are consistently the warmest within the context of the past 561 years exceeding the 1951−1980 mean of +1.3 °C. Cool summers across MANE were frequently volcanically forced, with significant ( p <0.05) temperature departures associated with 80% of the largest tropical ( n =13) and extratropical ( n =15) eruptions since 1461 CE. Yet, we find that more of the identified cool events in the record were likely unforced by volcanism and either related to stochastic variability or atmospheric circulation via significant associations ( p <0.05) to regional, coastal sea-surface temperatures, 500-hpa geopotential height, and 300-hpa meridional and zonal wind vectors. Expanding the MANE network to the west and south and combining it with existing temperature-sensitive proxies across North America is an important next step toward producing a gridded temperature reconstruction field for North America.

Association of diet with per- and polyfluoroalkyl substances in plasma and human milk in the New Hampshire Birth Cohort Study - Yuting Wang; Jiang Gui; Caitlin G. Howe; Jennifer A. Emond; Rachel L. Criswell; Lisa G. Gallagher; Carin A. Huset; Lisa A. Peterson; Julianne Cook Botelho; Antonia M. Calafat; Brock Christensen; Margaret R. Karagas; et al. (Science of The Total Environment, 2024)

An analysis of culture-based methods used for the detection and isolation of Salmonella spp., Escherichia coli, and Enterococcus spp. from surface water: A systematic review - Betty R. McConn; Autumn L. Kraft; Lisa M. Durso; Abasiofiok M. Ibekwe; Jonathan G. Frye; James E. Wells; Elizabeth M. Tobey; Stephanie Ritchie; Clinton F. Williams; Kimberly L. Cook; Manan Sharma (Science of The Total Environment, 2024)

Plasma per- and polyfluoroalkyl substance mixtures during pregnancy and duration of breastfeeding in the New Hampshire birth cohort study - Megan E. Romano; Lisa G. Gallagher; George Price; Kathryn A. Crawford; Rachel Criswell; Emily Baker; Julianne Cook Botelho; Antonia M. Calafat; Margaret R. Karagas (International Journal of Hygiene and Environmental Health, 2024)

A tale of 3 dwarf planets: Ices and organics on Sedna, Gonggong, and Quaoar from JWST spectroscopy - J.P. Emery; I. Wong; R. Brunetto; J.C. Cook; N. Pinilla-Alonso; J.A. Stansberry; B.J. Holler; W.M. Grundy; S. Protopapa; A.C. Souza-Feliciano; E. Fernández-Valenzuela; J.I. Lunine; et al. (Icarus, 2024)

Extraordinary levels of per- and polyfluoroalkyl substances (PFAS) in vertebrate animals at a New Mexico desert oasis: Multiple pathways for wildlife and human exposure - Christopher C. Witt; Chauncey R. Gadek; Jean-Luc E. Cartron; Michael J. Andersen; Mariel L. Campbell; Marialejandra Castro-Farías; Ethan F. Gyllenhaal; Andrew B. Johnson; Jason L. Malaney; Kyana N. Montoya; Andrew Patterson; Nicholas T. Vinciguerra; et al. (Environmental Research, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Horizon scanning of potential threats to high‐Arctic biodiversity, human health and the economy from marine invasive alien species: A Svalbard case study - Elizabeth J. Cottier‐Cook; Jude Bentley‐Abbot; Finlo R. Cottier; Dan Minchin; Sergej Olenin; Paul E. Renaud (Global Change Biology, 2024)
The high Arctic is considered a pristine environment compared with many other regions in the northern hemisphere. It is becoming increasingly vulnerable to invasion by invasive alien species (IAS), however, as climate change leads to rapid loss of sea ice, changes in ocean temperature and salinity, and enhanced human activities. These changes are likely to increase the incidence of arrival and the potential for establishment of IAS in the region. To predict the impact of IAS, a group of experts in taxonomy, invasion biology and Arctic ecology carried out a horizon scanning exercise using the Svalbard archipelago as a case study, to identify the species that present the highest risk to biodiversity, human health and the economy within the next 10 years. A total of 114 species, currently absent from Svalbard, recorded once and/or identified only from environmental DNA samples, were initially identified as relevant for review. Seven species were found to present a high invasion risk and to potentially cause a significant negative impact on biodiversity and five species had the potential to have an economic impact on Svalbard. Decapod crabs, ascidians and barnacles dominated the list of highest risk marine IAS. Potential pathways of invasion were also researched, the most common were found associated with vessel traffic. We recommend (i) use of this approach as a key tool within the application of biosecurity measures in the wider high Arctic, (ii) the addition of this tool to early warning systems for strengthening existing surveillance measures; and (iii) that this approach is used to identify high‐risk terrestrial and freshwater IAS to understand the overall threat facing the high Arctic. Without the application of biosecurity measures, including horizon scanning, there is a greater risk that marine IAS invasions will increase, leading to unforeseen changes in the environment and economy of the high Arctic.

A comparison of methods to detect low levels of Salmonella enterica in surface waters to support antimicrobial resistance surveillance efforts performed in multiple laboratories - Autumn L. Kraft; Jim E. Wells; Jonathan G. Frye; Abasiofiok M. Ibekwe; Lisa M. Durso; Lari Hiott; Cheryl East; Betty R. McConn; Alison M. Franklin; Laura A. Boczek; Jay L. Garland; Claudine Kabera; et al. (Science of The Total Environment, 2023)

Neurodevelopmental outcomes in children and adults with Fetal Valproate Spectrum Disorder: A contribution from the ConcePTION project - M. Bluett-Duncan; D. Astill; R. Charbak; J. Clayton-Smith; S. Cole; P.A. Cook; J. Cozens; K. Keely; J. Morris; R. Mukherjee; E. Murphy; P. Turnpenny; et al. (Neurotoxicology and Teratology, 2023)

Using in-situ strain measurements to evaluate the accuracy of stress estimation procedures from fracture injection/shut-in tests - Yves Guglielmi; Mark McClure; Jeffrey Burghardt; Joseph P. Morris; Thomas Doe; Pengcheng Fu; Hunter Knox; Vince Vermeul; Tim Kneafsey; J. Ajo-Franklin; T. Baumgartner; K. Beckers; et al. (International Journal of Rock Mechanics and Mining Sciences, 2023)

Correction: Long-chain omega-3 polyunsaturated fatty acids decrease mammary tumor growth, multiorgan metastasis and enhance survival - Saraswoti Khadge; Geoffrey M. Thiele; John Graham Sharp; Timothy R. McGuire; Lynell W. Klassen; Paul N. Black; Concetta C. DiRusso; Leah Cook; James E. Talmadge (Clinical & Experimental Metastasis, 2023)

The influence of complex matrices on method performance in extracting and monitoring for microplastics - Leah M. Thornton Hampton; Hannah De Frond; Kristine Gesulga; Syd Kotar; Wenjian Lao; Cindy Matuch; Stephen B. Weisberg; Charles S. Wong; Susanne Brander; Silke Christansen; Cayla R. Cook; Fangni Du; et al. (Chemosphere, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Metals and per- and polyfluoroalkyl substances mixtures and birth outcomes in the New Hampshire Birth Cohort Study: Beyond single-class mixture approaches - Gyeyoon Yim; Glen McGee; Lisa Gallagher; Emily Baker; Brian P. Jackson; Antonia M. Calafat; Julianne Cook Botelho; Diane Gilbert-Diamond; Margaret R. Karagas; Megan E. Romano; Caitlin G. Howe (Chemosphere, 2023)

Grazing, egg production and carbon budgets for Calanus finmarchicus across the Fram Strait - Holly E. Jenkins; Florence Atherden; Kathryn B. Cook; Thomas R. Anderson; Barry Thornton; Elaine Mitchell; Elodie Jacob; Daniel J. Mayor (Frontiers in Marine Science, 2022)
Calanoid copepods comprise around 90% of Arctic zooplankton biomass and are fundamental to the ecological and biogeochemical functioning of high-latitude pelagic ecosystems. They accumulate lipid reserves during the productive months and represent an energy-rich food source for higher trophic levels. Rapidly changing climate in the Arctic may alter the quantity and composition of the food environment for one of the key copepod species, Calanus finmarchicus , with as yet unquantified effects on its production. Here we present rates of feeding and egg production in female C. finmarchicus exposed to the range of feeding conditions encountered across the Fram Strait in May/June 2018. Carbon (C) budgets were constructed and used to examine the relationship between feeding and growth (= egg production) in these animals. C-specific ingestion rates (mean ± standard deviation) were highly variable, ranging from 0.015 ± 0.004 to 0.645 ± 0.017 day -1 (mean = 0.295 ± 0.223 day -1 ), and were positively correlated with food availability. C-specific egg production rates ranged from 0.00 to 0.049 day -1 (mean = 0.012 ± 0.011) and were not correlated with either food availability or ingestion rate. Calculated gross growth efficiencies (GGE: growth/ingestion) were low, 0.12 ± 0.13 (range = 0.01 to 0.39). The assembled C budgets indicate that the average fraction of ingested food that was surplus to the requirements for egg production, respiration and losses to faecal pellets was 0.17 ± 0.42. We suggest that this excess occurred, at least in part, because many of the incubated females were still undergoing the energetically (C-) expensive process of gonad maturation at the time of sampling, an assertion that is supported by the relatively high C:N (nitrogen) ratios of the incubated females, the typically low egg production rates, and gonad maturation status. Ontogenetic development may thus explain the large variability seen in the relationship between egg production and ingestion. The apparently excessive ingestion rates may additionally indicate that recently moulted females must acquire additional N via ingestion to complete the maturation process and begin spawning. Our results highlight the need for improved fundamental understanding of the physiology of high-latitude copepods and its response to environmental change.

A Case Study of Large Floodplain River Restoration: Two Decades of Monitoring the Merwin Preserve and Lessons Learned through Water Level Fluctuations and Uncontrolled Reconnection to a Large River - Levi E. Solomon; Andrew F. Casper; Kristopher A. Maxson; James T. Lamer; Trent W. Ford; K. Douglass Blodgett; Tharran Hobson; Denim Perry; Nathan T. Grider; Rob B. Hilsabeck; Thad R. Cook; Kevin S. Irons; et al. (Wetlands, 2022)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Carbon and Lipid Contents of the Copepod Calanus finmarchicus Entering Diapause in the Fram Strait and Their Contribution to the Boreal and Arctic Lipid Pump - Geraint A. Tarling; Anna Belcher; Mayleen Blackwell; Claudia Castellani; Kathryn Barbara Cook; Finlo R. Cottier; Victoria Dewar-Fowler; Jennifer J. Freer; Laura Gerrish; Magnus L. Johnson; Kim S. Last; Penelope Kate Lindeque; et al. (Frontiers in Marine Science, 2022)
The boreal copepod Calanus finmarchicus sequesters substantial amounts of carbon (C) in the deep layers of the North Atlantic Ocean through their contribution to the “lipid pump.” This pump is driven by these zooplankton descending from the surface layers to spend prolonged periods at depth during which time they metabolise substantial lipid reserves and a fraction suffer mortality. C. finmarchicus is principally a boreal species but is expatriated by currents flowing northwards into Arctic regions such as the Fram Strait, where it is now able to complete its life cycle. We considered how this expansion to its distributional range adds to the estimated magnitude of the lipid pump. Field sampling in the Fram Strait found C. finmarchicus abundance to be spatially variable with high values, equivalent to those reported for core distributional areas further south, found mainly in the eastern region. Lipid reserve levels were sufficient for many individuals to survive the overwintering period and reproduce the following spring. In accordance with abundance patterns, lipid pump magnitude was greater in the Eastern Fram Strait (2.04 g C m −2 year −1 ) compared to the Western Fram Strait (0.33 g C m −2 year −1 ). At least for the eastern region, these rates are similar to those reported for this species elsewhere (average of 4.35 g C m −2 year −1 ). When extrapolated to the wider spatial area of the Fram Strait, the lipid pump generated by this species in this ocean sector amounts to 0.3 Mt C year −1 . Although constituting a modest proportion of the total C. finmarchicus lipid pump of 19.3 Mt C year −1 , it indicates that the continued northwards expansion of this species will act to increase the size of its lipid pump, which may counteract that lost through the northwards retreat of its Arctic congeners, Calanus glacialis and Calanus hyperboreus .

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Expert range maps of global mammal distributions harmonised to three taxonomic authorities - Charles J. Marsh; Yanina V. Sica; Connor J. Burgin; Wendy A. Dorman; Robert C. Anderson; Isabel del Toro Mijares; Jessica G. Vigneron; Vijay Barve; Victoria L. Dombrowik; Michelle Duong; Robert Guralnick; Julie A. Hart; et al. (Journal of Biogeography, 2022)
Aim Comprehensive, global information on species' occurrences is an essential biodiversity variable and central to a range of applications in ecology, evolution, biogeography and conservation. Expert range maps often represent a species' only available distributional information and play an increasing role in conservation assessments and macroecology. We provide global range maps for the native ranges of all extant mammal species harmonised to the taxonomy of the Mammal Diversity Database (MDD) mobilised from two sources, the Handbook of the Mammals of the World (HMW) and the Illustrated Checklist of the Mammals of the World (CMW). Location Global. Taxon All extant mammal species. Methods Range maps were digitally interpreted, georeferenced, error‐checked and subsequently taxonomically aligned between the HMW (6253 species), the CMW (6431 species) and the MDD taxonomies (6362 species). Results Range maps can be evaluated and visualised in an online map browser at Map of Life ( mol.org ) and accessed for individual or batch download for non‐commercial use. Main conclusion Expert maps of species' global distributions are limited in their spatial detail and temporal specificity, but form a useful basis for broad‐scale characterizations and model‐based integration with other data. We provide georeferenced range maps for the native ranges of all extant mammal species as shapefiles, with species‐level metadata and source information packaged together in geodatabase format. Across the three taxonomic sources our maps entail, there are 1784 taxonomic name differences compared to the maps currently available on the IUCN Red List website. The expert maps provided here are harmonised to the MDD taxonomic authority and linked to a community of online tools that will enable transparent future updates and version control.

Rapid radiation of Southern Ocean shags in response to receding sea ice - Nicolas J. Rawlence; Alexander T. Salis; Hamish G. Spencer; Jonathan M. Waters; Lachie Scarsbrook; Kieren J. Mitchell; Richard A. Phillips; Luciano Calderón; Timothée R. Cook; Charles‐André Bost; Ludovic Dutoit; Tania M. King; et al. (Journal of Biogeography, 2022)
Aim Understanding how natural populations respond to climatic shifts is a fundamental goal of biological research in a fast‐changing world. The Southern Ocean represents a fascinating system for assessing large‐scale climate‐driven biological change, as it contains extremely isolated island groups within a predominantly westerly, circumpolar wind and current system. Blue‐eyed shags represent a paradoxical seabird radiation—a circumpolar distribution implies strong dispersal capacity yet their species‐rich nature suggests local adaptation and isolation. Here we attempt to resolve this paradox in light of the history of repeated cycles of climate change in the Southern Ocean. Location Southern Ocean. Taxa 16 species and subspecies of blue‐eyed shags (Phalacrocoracidae; Leucocarbo spp.). Methods We use mitochondrial and nuclear sequence data from individuals across the geographical range of the genus to conduct the first comprehensive, time‐calibrated phylogenetic analyses and ancestral‐range biogeographical reconstructions of the blue‐eyed shags. Results The origins of many island‐endemic lineages are remarkably recent, consistent with a recent high‐latitude circumpolar radiation in the Pliocene or Early Pleistocene. This recent sub‐Antarctic expansion contrasts with significantly deeper lineages detected in South America and, to a lesser extent, New Zealand. These regions, particularly South America, acted as glacial refugia and sources for multiple waves of post‐glacial dispersal. Main conclusions The blue‐eyed shag paradox is resolved, with at least two waves of dispersal, linked to interglacial cycles, explaining the current distribution and diversity. Descendants of a Pliocene or Early Pleistocene wave of dispersal out of South America survive in the New Zealand region. In contrast, taxa distributed on sub‐Antarctic islands originated much later, possibly since the Last Glacial Maximum. Blue‐eyed shags therefore represent a powerful model system—comprising several natural replicates—for studying the early stages of founder‐event speciation and adaptation in a Southern‐Ocean bird group.

Changing hydroclimate dynamics and the 19th to 20th century wetting trend in the English Channel region of northwest Europe - Serena R. Scholz; Richard Seager; Mingfang Ting; Yochanan Kushnir; Jason E. Smerdon; Benjamin I. Cook; Edward R. Cook; Seung Hun Baek (Climate Dynamics, 2022)

The Alberta moving beyond breast cancer (AMBER) cohort study: baseline description of the full cohort - Christine M. Friedenreich; Jeff K. Vallance; Margaret L. McNeely; S. Nicole Culos-Reed; Charles E. Matthews; Gordon J. Bell; John R. Mackey; Karen A. Kopciuk; Leanne Dickau; Qinggang Wang; Diane Cook; Stephanie Wharton; et al. (Cancer Causes & Control, 2022)
Purpose The Alberta Moving Beyond B r east Cancer (AMBER) Study is an ongoing prospective cohort study investigating how direct measures of physical activity (PA), sedentary behavior (SB), and health-related fitness (HRF) are associated with survival after breast cancer. Methods Women in Alberta with newly diagnosed stage I (≥ T1c) to IIIc breast cancer were recruited between 2012 and 2019. Baseline assessments were completed within 90 days of surgery. Measurements included accelerometers to measure PA and SB; a graded treadmill test with gas exchange analysis to measure cardiorespiratory fitness (VO 2peak ); upper and lower body muscular strength and endurance; dual-X-ray absorptiometry to measure body composition; and questionnaires to measure self-reported PA and SB. Results At baseline, the 1528 participants’ mean age was 56 ± 11 years, 59% were post-menopausal, 62% had overweight/obesity, and 55% were diagnosed with stage II or III disease. Based on device measurements, study participants spent 8.9 ± 1.7 h/day sedentary, 4.4 ± 1.2 h/day in light-intensity activity, 0.9 ± 0.5 h/day in moderate-intensity activity, and 0.2 ± 0.2 h/day in vigorous-intensity activity. For those participants who reached VO 2peak , the average aerobic fitness level was 26.6 ± 6 ml/kg/min. Average body fat was 43 ± 7.1%. Conclusion We have established a unique cohort of breast cancer survivors with a wealth of data on PA, SB, and HRF obtained through both direct and self-reported measurements. Study participants are being followed for at least ten years to assess all outcomes after breast cancer. These data will inform clinical and public health guidelines on PA, SB, and HRF for improving breast cancer outcomes.

Can a key boreal Calanus copepod species now complete its life-cycle in the Arctic? Evidence and implications for Arctic food-webs - Geraint A. Tarling; Jennifer J. Freer; Neil S. Banas; Anna Belcher; Mayleen Blackwell; Claudia Castellani; Kathryn B. Cook; Finlo R. Cottier; Malin Daase; Magnus L. Johnson; Kim S. Last; Penelope K. Lindeque; et al. (Ambio, 2022)
The changing Arctic environment is affecting zooplankton that support its abundant wildlife. We examined how these changes are influencing a key zooplankton species, Calanus finmarchicus , principally found in the North Atlantic but expatriated to the Arctic. Close to the ice-edge in the Fram Strait, we identified areas that, since the 1980s, are increasingly favourable to C. finmarchicus . Field-sampling revealed part of the population there to be capable of amassing enough reserves to overwinter. Early developmental stages were also present in early summer, suggesting successful local recruitment. This extension to suitable C. finmarchicus habitat is most likely facilitated by the long-term retreat of the ice-edge, allowing phytoplankton to bloom earlier and for longer and through higher temperatures increasing copepod developmental rates. The increased capacity for this species to complete its life-cycle and prosper in the Fram Strait can change community structure, with large consequences to regional food-webs.

Geographic variation of mercury in breeding tidal marsh sparrows of the northeastern United States - Christopher J. Sayers; Mackenzie R. Roeder; Lindsay M. Forrette; Daniel Roche; Gaetan L. B. Dupont; Sam E. Apgar; Alison R. Kocek; Alexandra M. Cook; W. Gregory Shriver; Chris S. Elphick; Brian Olsen; David N. Bonter (Ecotoxicology, 2021)

Trace Element Patterns in Otoliths: The Role of Biomineralization - Karin Hüssy; Karin E. Limburg; Hélène de Pontual; Oliver R. B. Thomas; Philip K. Cook; Yvette Heimbrand; Martina Blass; Anna M. Sturrock (Reviews in Fisheries Science & Aquaculture, 2021)

The Toxicology Investigators Consortium 2020 Annual Report - Meghan B. Spyres; Kim Aldy; Lynn A Farrugia; A. Min Kang; Jennifer S. Love; Sharan L. Campleman; Shao Li; Alexandra Amaducci; Evan Schwarz; Paul M. Wax; Jeffery Brent; J. Acciani; et al. (Journal of Medical Toxicology, 2021)

Seaweed aquaculture: a preliminary assessment of biosecurity measures for controlling the ice-ice syndrome and pest outbreaks of a Kappaphycus farm - Cicilia S. B. Kambey; Iona Campbell; Elizabeth J. Cottier-Cook; Adibi R. M. Nor; Azhar Kassim; Ahemad Sade; Phaik E. Lim (Journal of Applied Phycology, 2021)
The application of biosecurity in seaweed aquaculture plays an important role in reducing the impact of disease and pest outbreaks. The continuous occurrence of seaweed pests including the macroalgal epiphytes, epi-endophytic filamentous algae and biofilms on Kappaphycus farms may also potentially induce further incidences of the ice-ice syndrome. In this study, on-farm biosecurity management measures were tested on the commercially grown seaweeds Kappaphycus malesianus and Kappaphycus alvarezii during peak ice-ice season at Gallam-Gallam Village, Sabah, Malaysia. The investigation was focused on preventative control measures including the early detection of the ice-ice syndrome and pests through propagule health checks, regular cleaning of the crop thallus and associated long-line ropes and monitoring of the environment. Farm procedures and practices were also assessed in terms of their biosecurity ‘risk’ using the hazard analysis and critical control point (HCCAP) approach. Observations were replicated in two different farm management systems; one system adopted routine biosecurity measures and the other had no biosecurity measures. The results showed that the ice-ice syndrome and pest outbreak was significantly decreased by 60–75% for K. malesianus and 29–71% for K. alvarezii at the farm which adopted the routine biosecurity measures compared with the no biosecurity treatment. The biosecurity measures also significantly improved growth rate and seaweed quality. The infection levels of the epi-endophyte Melanothamnus sp. contributed to the ice-ice syndrome in K. malesianus , whilst the epiphyte coverage was correlated to the ice-ice incidence in K. alvarezii . This study provides the first evidence of biosecurity management measures significantly decreasing the incidence of the ice-ice syndrome and pests on a commercial seaweed farm.

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

Cardiac response to adrenergic stress differs by sex and across the lifespan - Aykhan Yusifov; Vikram E. Chhatre; Jacob M. Zumo; Ross F. Cook; Benjamin D. McNair; Emily E. Schmitt; Kathleen C. Woulfe; Danielle R. Bruns (GeroScience, 2021)

Characteristics of Transgender Patient Cases Managed by a Toxicologist: an Analysis of the Toxicology Investigator’s Consortium (ToxIC) Registry: January 2017–June 2019 - Ryan M. Surmaitis; Marna Rayl Greenberg; Natalie E. Ebeling-Koning; Phillip M. Grenz; Cody R. McWhirter; Beth A. Careyva; Judith N. Sabino; Matthew D. Cook; Robert D. Cannon; Andrew L. Koons; Kenneth D. Katz; Hope Kincaid; et al. (Journal of Medical Toxicology, 2021)

Low Static Shear Modulus Along Foliation and Its Influence on the Elastic and Strength Anisotropy of Poorman Schist Rocks, Homestake Mine, South Dakota - Katherine J. Condon; Hiroki Sone; Herbert F. Wang; J. Ajo-Franklin; T. Baumgartner; K. Beckers; D. Blankenship; A. Bonneville; L. Boyd; S. Brown; J. A. Burghardt; C. Chai; et al. (Rock Mechanics and Rock Engineering, 2020)

Racial and ethnic differences in risk of second primary cancers among prostate cancer survivors - Diana R. Withrow; Sara J. Schonfeld; Rochelle E. Curtis; Lindsay M. Morton; Michael B. Cook; Eboneé N. Butler; Amy Berrington de González (Cancer Causes & Control, 2020)

Taxon pulse dynamics, episodic dispersal and host colonization across Beringia drive diversification of a Holarctic tapeworm assemblage - Genevieve M. S. Haas; Eric P. Hoberg; Joseph A. Cook; Heikki Henttonen; Arseny A. Makarikov; Sarah R. Gallagher; Nikolai E. Dokuchaev; Kurt E. Galbreath (Journal of Biogeography, 2020)
Aim We test the predictions of the Stockholm Paradigm, a synthesis of eco‐evolutionary theory explaining the nature of faunal assembly, host range and parasite diversification. Faunal diversification and assembly, manifested in patterns of host colonization, co‐adaptation and parasite speciation, are predicted to emerge as a consequence of alternating episodes of ecological disruption and stability. Specifically, for a diverse cestode genus ( Arostrilepis ), we evaluate the number and direction of Pleistocene dispersal events across Beringia, the number and relative timing of host colonization events and the relationship between host and parasite biogeographic histories and associations through time. Location Beringia and adjacent temperate to arctic biomes in North America and Eurasia. Taxon Arostrilepis (Cyclophyllidea: Hymenolepididae) and its rodent hosts. Methods Multi‐locus phylogenetic reconstruction and biogeographic ancestral range estimation. Results Arostrilepis lineages crossed Beringia eastward into North America a minimum of four times and westward into Asia twice in association with temporally disjunct geographic expansions of three major tribes of cricetid rodents (Arvicolini, Myodini, Lemmini). Inferences of ancestral host associations support at least nine instances of host colonization involving shifts from one rodent tribe or family to another. Several previously unrecognized lineages of Arostrilepis are revealed. Main conclusions Consistent with expectations of the Stockholm Paradigm, episodes of intercontinental dispersal were both frequent in the history of Arostrilepis and preceded a majority of inferred host‐colonization events. Events of historical geographic expansion created numerous opportunities for development of novel host–parasite associations through ecological fitting, as parasites tracked historically conserved resources available across diverse host taxa. Beringia played a major role in shaping rodent/parasite assemblages by mediating dispersal between the northern continents during glacial episodes of the Pleistocene, rather than by serving as a zone of refugial isolation.

An analysis of the current status and future of biosecurity frameworks for the Indonesian seaweed industry - Cicilia S. B. Kambey; Iona Campbell; Calvyn F. A. Sondak; Adibi R. M. Nor; Phaik E. Lim; Elizabeth J. Cottier-Cook (Journal of Applied Phycology, 2020)
Indonesia is the world largest producer of the red seaweeds Kappaphycus and Eucheuma ; however, this country is facing significant challenges such as disease outbreaks, epiphyte infestations and a loss in seedling quality. Biosecurity practices have been widely adopted in other aquaculture sectors and when enforced can help to limit the introduction and spread of diseases and pests. To assess current capacity for biosecurity in seaweed aquaculture in Indonesia, a systematic analysis of policy frameworks including legislation, regulatory tools, and national standards was conducted. Biosecurity themes and risks were used to evaluate current national biosecurity content. The results identified major challenges faced by the industry in order to implement biosecurity policies in practice. Barriers to implementation included unspecific reference to the seaweed aquaculture sector, limited variety of approaches to biosecurity, limited use of up-to-date scientific evidence, insufficient guidance for the use of precaution and insufficient inclusion of specific biosecurity hazards. In general, although national regulations are currently under revision, current policies indicate a lack of clarity where biosecurity is included. Six recommendations are suggested to incorporate proactive biosecurity actions into current frameworks, with the aim of improving the health and sustainability of the seaweed aquaculture sector in Indonesia.

The global Microcystis interactome - Katherine V. Cook; Chuang Li; Haiyuan Cai; Lee R. Krumholz; K. David Hambright; Hans W. Paerl; Morgan M. Steffen; Alan E. Wilson; Michele A. Burford; Hans‐Peter Grossart; David P. Hamilton; Helong Jiang; et al. (Limnology and Oceanography, 2020)
Bacteria play key roles in the function and diversity of aquatic systems, but aside from study of specific bloom systems, little is known about the diversity or biogeography of bacteria associated with harmful cyanobacterial blooms (cyanoHABs). CyanoHAB species are known to shape bacterial community composition and to rely on functions provided by the associated bacteria, leading to the hypothesized cyanoHAB interactome, a coevolved community of synergistic and interacting bacteria species, each necessary for the success of the others. Here, we surveyed the microbiome associated with Microcystis aeruginosa during blooms in 12 lakes spanning four continents as an initial test of the hypothesized Microcystis interactome. We predicted that microbiome composition and functional potential would be similar across blooms globally. Our results, as revealed by 16S rRNA sequence similarity, indicate that M. aeruginosa is cosmopolitan in lakes across a 280° longitudinal and 90° latitudinal gradient. The microbiome communities were represented by a wide range of operational taxonomic units and relative abundances. Highly abundant taxa were more related and shared across most sites and did not vary with geographic distance, thus, like Microcystis , revealing no evidence for dispersal limitation. High phylogenetic relatedness, both within and across lakes, indicates that microbiome bacteria with similar functional potential were associated with all blooms. While Microcystis and the microbiome bacteria shared many genes, whole‐community metagenomic analysis revealed a suite of biochemical pathways that could be considered complementary. Our results demonstrate a high degree of similarity across global Microcystis blooms, thereby providing initial support for the hypothesized Microcystis interactome.

Toward the Integrated Marine Debris Observing System - Nikolai Maximenko; Paolo Corradi; Kara Lavender Law; Erik Van Sebille; Shungudzemwoyo P. Garaba; Richard Stephen Lampitt; Francois Galgani; Victor Martinez-Vicente; Lonneke Goddijn-Murphy; Joana Mira Veiga; Richard C. Thompson; Christophe Maes; et al. (Frontiers in Marine Science, 2019)

Foundations and Frontiers of Ecosystem Science: Legacy of a Classic Paper (Odum 1969) - Jessica R. Corman; Scott L. Collins; Elizabeth M. Cook; Xiaoli Dong; Laureano A. Gherardi; Nancy B. Grimm; Rebecca L. Hale; Tao Lin; Jorge Ramos; Lara G. Reichmann; Osvaldo E. Sala (Ecosystems, 2019)

A Euro-Mediterranean tree-ring reconstruction of the winter NAO index since 910 C.E. - Edward R. Cook; Yochanan Kushnir; Jason E. Smerdon; A. Park Williams; Kevin J. Anchukaitis; Eugene R. Wahl (Climate Dynamics, 2019)

Tree-ring reconstructions of cool season temperature for far southeastern Australia, 1731–2007 - K. J. Allen; K. J. Anchukaitis; M. G. Grose; G. Lee; E. R. Cook; J. S. Risbey; T. J. O’Kane; D. Monselesan; A. O’Grady; S. Larsen; P. J. Baker (Climate Dynamics, 2019)

Implementation of a Systematic Tumor Screening Program for Lynch Syndrome in an Integrated Health Care Setting - Elizabeth V. Clarke; Kristin R. Muessig; Jamilyn Zepp; Jessica E. Hunter; Sapna Syngal; Louise S. Acheson; Georgia L. Wiesner; Susan K. Peterson; Kellene M. Bergen; Elizabeth Shuster; James V. Davis; Jennifer L. Schneider; et al. (Familial Cancer, 2019)

Forest Fertilizer Applications in the Southeastern United States from 1969 to 2016 - Timothy J Albaugh; Thomas R Fox; Rachel L Cook; Jay E Raymond; Rafael A Rubilar; Otávio C Campoe (Forest Science, 2019)

How do climate change experiments alter plot‐scale climate? - A. K. Ettinger; I. Chuine; B. I. Cook; J. S. Dukes; A. M. Ellison; M. R. Johnston; A. M. Panetta; C. R. Rollinson; Y. Vitasse; E. M. Wolkovich (Ecology Letters, 2019)
To understand and forecast biological responses to climate change, scientists frequently use field experiments that alter temperature and precipitation. Climate manipulations can manifest in complex ways, however, challenging interpretations of biological responses. We reviewed publications to compile a database of daily plot‐scale climate data from 15 active‐warming experiments. We find that the common practices of analysing treatments as mean or categorical changes (e.g. warmed vs. unwarmed) masks important variation in treatment effects over space and time. Our synthesis showed that measured mean warming, in plots with the same target warming within a study, differed by up to 1.6 C (63% of target), on average, across six studies with blocked designs. Variation was high across sites and designs: for example, plots differed by 1.1 C (47% of target) on average, for infrared studies with feedback control ( n = 3) vs. by 2.2 C (80% of target) on average for infrared with constant wattage designs ( n = 2). Warming treatments produce non‐temperature effects as well, such as soil drying. The combination of these direct and indirect effects is complex and can have important biological consequences. With a case study of plant phenology across five experiments in our database, we show how accounting for drier soils with warming tripled the estimated sensitivity of budburst to temperature. We provide recommendations for future analyses, experimental design, and data sharing to improve our mechanistic understanding from climate change experiments, and thus their utility to accurately forecast species’ responses.

Long-chain omega-3 polyunsaturated fatty acids decrease mammary tumor growth, multiorgan metastasis and enhance survival - Saraswoti Khadge; Geoffrey M. Thiele; John Graham Sharp; Timothy R. McGuire; Lynell W. Klassen; Paul N. Black; Concetta C. DiRusso; Leah Cook; James E. Talmadge (Clinical & Experimental Metastasis, 2018)

Genome-wide association study of primary open-angle glaucoma in continental and admixed African populations - Pieter W. M. Bonnemaijer; Adriana I. Iglesias; Girish N. Nadkarni; Anna J. Sanyiwa; Hassan G. Hassan; Colin Cook; Mark Simcoe; Kent D. Taylor; Claudia Schurmann; Gillian M. Belbin; Eimear E. Kenny; Erwin P. Bottinger; et al. (Human Genetics, 2018)

Can we increase smokers’ adherence to nicotine replacement therapy and does this help them quit? - Tanya R. Schlam; Jessica W. Cook; Timothy B. Baker; Todd Hayes-Birchler; Daniel M. Bolt; Stevens S. Smith; Michael C. Fiore; Megan E. Piper (Psychopharmacology, 2018)

Trends of two HPV-associated cancers in Massachusetts: cervical and oropharyngeal cancer - Erin E. Cook; Susan T. Gershman; Jane J. Kim; Rulla M. Tamimi; R. Monina Klevens; Michelle D. Holmes (Cancer Causes & Control, 2018)

Agro-morphological traits of Cicer reticulatum Ladizinsky in comparison to C. echinospermum P.H. Davis in terms of potential to improve cultivated chickpea (C. arietinum L.) - Mirlan Talip; Alper Adak; Abdullah Kahraman; Jens Berger; Duygu Sari; Hatice Sari; R. V. Penmetsa; E. J. von Wettberg; D. R. Cook; Cengiz Toker (Genetic Resources and Crop Evolution, 2018)

Universal screening for Lynch syndrome among patients with colorectal cancer: patient perspectives on screening and sharing results with at-risk relatives - Jessica Ezzell Hunter; Kathleen A. Arnold; Jennifer E. Cook; Jamilyn Zepp; Marian J. Gilmore; Alan F. Rope; James V. Davis; Kellene M. Bergen; Elizabeth Esterberg; Kristin R. Muessig; Susan K. Peterson; Sapna Syngal; et al. (Familial Cancer, 2017)

Virological Quality of Irrigation Water in Leafy Green Vegetables and Berry Fruits Production Chains - P. Kokkinos; I. Kozyra; S. Lazic; K. Söderberg; P. Vasickova; M. Bouwknegt; S. Rutjes; K. Willems; R. Moloney; A. M. de Roda Husman; A. Kaupke; E. Legaki; et al. (Food and Environmental Virology, 2017)

Spatial reconstruction of Scottish summer temperatures from tree rings - Miloš Rydval; Björn E. Gunnarson; Neil J. Loader; Edward R. Cook; Daniel L. Druckenbrod; Rob Wilson (International Journal of Climatology, 2017)
A detailed understanding of past temporal patterns and spatial expression of temperature variations is important to place recent anthropogenic climate change into a longer term context. In order to fill the current gap in our understanding of northwest European temperature variability, point‐by‐point principal component regression was used to reconstruct a spatial field of 0.5° temperature grids across Scotland. A sequence of reconstructions utilizing several combinations of detrending and disturbance correction procedures, and a selection of tree‐ring parameters [including ring width ( RW ), maximum latewood density ( MXD ) and blue intensity ( BI )] was used in an evaluation of reconstruction skill. The high resolution of the reconstructed field serves also as a diagnostic tool to spatially assess the temperature reconstruction potential of local chronologies. Best reconstruction results, reaching calibration r 2 = 65.8% and verification r 2 = 63.7% in central Scotland over the 1901–1976 period, were achieved using disturbance‐corrected and signal‐free detrended RW chronologies merged with BI data after low‐pass (high‐pass) filtering the RW ( BI ) chronologies. Calibration and verification r 2 > 50% was attained for central, north and east Scotland, >40% in west and northwest, and >30% in southern Scotland with verification of nearly all grids showing some reconstruction skill. However, the full calibration potential of reconstructions outside central Scotland was reduced either due to residual disturbance trends undetected by the disturbance correction procedure or due to other climatic or non‐climatic factors which may have adversely affected the strength of the climate signal.

Meta-studies in land use science: Current coverage and prospects - Jasper van Vliet; Nicholas R. Magliocca; Bianka Büchner; Elizabeth Cook; José M. Rey Benayas; Erle C. Ellis; Andreas Heinimann; Eric Keys; Tien Ming Lee; Jianguo Liu; Ole Mertz; Patrick Meyfroidt; et al. (Ambio, 2016)

Reconstruction of the springtime East Asian Subtropical Jet and Western Pacific pattern from a millennial-length Taiwanese tree-ring chronology - W. E. Wright; B. T. Guan; Y.-H. Tseng; E. R. Cook; K.-Y. Wei; S.-T. Chang (Climate Dynamics, 2015)

Genome-wide association study of subtype-specific epithelial ovarian cancer risk alleles using pooled DNA - Madalene A. Earp; Linda E. Kelemen; Anthony M. Magliocco; Kenneth D. Swenerton; Georgia Chenevix-Trench; Yi Lu; Alexander Hein; Arif B. Ekici; Matthias W. Beckmann; Peter A. Fasching; Diether Lambrechts; Evelyn Despierre; et al. (Human Genetics, 2014)

Turning passive detection systems into field experiments: an application using wetland fishes and enclosures to track fine-scale movement and habitat choice - J. S. Rehage; R. E. Boucek; E. A. Cline; M. I. Cook; R. M. Kobza; A. K. Saha (acta ethologica, 2014)

Genome-wide association study of endometrial cancer in E2C2 - Immaculata De Vivo; Jennifer Prescott; Veronica Wendy Setiawan; Sara H. Olson; Nicolas Wentzensen; John Attia; Amanda Black; Louise Brinton; Chu Chen; Constance Chen; Linda S. Cook; Marta Crous-Bou; et al. (Human Genetics, 2014)

Effect of the duration of inoculum exposure on development of citrus canker symptoms on seedlings of Swingle citrumelo - Clive H. Bock; James H. Graham; Tim R. Gottwald; Amanda Z. Cook; Paul E. Parker (European Journal of Plant Pathology, 2014)

Colony social structure in native and invasive populations of the social wasp Vespula pensylvanica - Cause Hanna; Erin D. Cook; Ariel R. Thompson; Lyndzey E. Dare; Amanda L. Palaski; David Foote; Michael A. D. Goodisman (Biological Invasions, 2014)

Reliability of individual and pooled test procedures for detecting the pathogenic agent for clinical infectious salmon anaemia - M Hall; I S Wallace; L A Munro; E S Munro; R McIntosh; P Cook; C E T Allan; A G Murray (Journal of Fish Diseases, 2013)

A strong regional temperature signal in low‐elevation Huon pine - K. J. ALLEN; D. M. DREW; G. M. DOWNES; R. EVANS; E. R. COOK; M. BATTAGLIA; P. J. BAKER (Journal of Quaternary Science, 2013)
We have produced the first annually resolved, centennial‐length tree‐ring chronologies, based on tracheid radial diameter (TRD) and microfibril angle for south‐eastern Australia (SEA) from what would commonly be considered a dendroclimatically suboptimal site. The chronologies exhibit a strong regional temperature signal for the austral summer (nominally November–April) that extends across much of SEA. The strength and spatial extent of the temperature–TRD correlations surpass those between the iconic Tasmanian Mt Read ring‐width chronology and austral summer temperatures, and are more time‐stable. We demonstrate that the value of wood property chronologies for their ability to improve the both the quality and the quantity of highly climate‐sensitive series available for regional annual‐resolution climate reconstructions, in data‐sparse regions in Australasia and beyond, should be examined. In light of the ‘divergence debate’, the time‐stability of relationships with climate, relative to other tree‐ring proxies, also requires further investigation.

A comparison of culture-dependent and culture-independent techniques used to characterize bacterial communities on healthy and white plague-diseased corals of the Montastraea annularis species complex - G. M. Cook; J. P. Rothenberger; M. Sikaroodi; P. M. Gillevet; E. C. Peters; R. B. Jonas (Coral Reefs, 2013)

Amycolatopsis umgeniensis sp. nov., isolated from soil from the banks of the Umgeni River in South Africa - Gareth J. Everest; Marilize le Roes-Hill; Clifford Omorogie; Shuk-Kwan Cheung; Andrew E. Cook; Candice M. Goodwin; Paul R. Meyers (Antonie van Leeuwenhoek, 2013)

Epidemiology of Helicobacter pylori infection in six Latin American countries (SWOG Trial S0701) - Carolina Porras; Jesse Nodora; Rachael Sexton; Catterina Ferreccio; Silvia Jimenez; Ricardo L. Dominguez; Paz Cook; Garnet Anderson; Douglas R. Morgan; Laurence H. Baker; E. Robert Greenberg; Rolando Herrero (Cancer Causes & Control, 2013)

Sensitivity of Spring Phenology to Warming Across Temporal and Spatial Climate Gradients in Two Independent Databases - Benjamin I. Cook; Elizabeth M. Wolkovich; T. Jonathan Davies; Toby R. Ault; Julio L. Betancourt; Jenica M. Allen; Kjell Bolmgren; Elsa E. Cleland; Theresa M. Crimmins; Nathan J. B. Kraft; Lesley T. Lancaster; Susan J. Mazer; et al. (Ecosystems, 2012)

Harmonised Investigation of the Occurrence of Human Enteric Viruses in the Leafy Green Vegetable Supply Chain in Three European Countries - P. Kokkinos; I. Kozyra; S. Lazic; M. Bouwknegt; S. Rutjes; K. Willems; R. Moloney; A. M. de Roda Husman; A. Kaupke; E. Legaki; M. D’Agostino; N. Cook; et al. (Food and Environmental Virology, 2012)

A novel approach of homozygous haplotype sharing identifies candidate genes in autism spectrum disorder - Jillian P. Casey; Tiago Magalhaes; Judith M. Conroy; Regina Regan; Naisha Shah; Richard Anney; Denis C. Shields; Brett S. Abrahams; Joana Almeida; Elena Bacchelli; Anthony J. Bailey; Gillian Baird; et al. (Human Genetics, 2012)

Ubiquitous Brms1 expression is critical for mammary carcinoma metastasis suppression via promotion of apoptosis - Leah M. Cook; Xuemei Cao; Alexander E. Dowell; Michael T. Debies; Mick D. Edmonds; Benjamin H. Beck; Robert A. Kesterson; Renee A. Desmond; Andra R. Frost; Douglas R. Hurst; Danny R. Welch (Clinical & Experimental Metastasis, 2012)

Macronutrient regulation in the Rasberry crazy ant (Nylanderia sp. nr. pubens) - S. C. Cook; R. A. Wynalda; R. E. Gold; S. T. Behmer (Insectes Sociaux, 2012)

Haplotype structure in Ashkenazi Jewish BRCA1 and BRCA2 mutation carriers - Kate M. Im; Tomas Kirchhoff; Xianshu Wang; Todd Green; Clement Y. Chow; Joseph Vijai; Joshua Korn; Mia M. Gaudet; Zachary Fredericksen; V. Shane Pankratz; Candace Guiducci; Andrew Crenshaw; et al. (Human Genetics, 2011)

The potential to reconstruct broadscale climate indices associated with southeast Australian droughts from Athrotaxis species, Tasmania - K. J. Allen; J. Ogden; B. M. Buckley; E. R. Cook; P. J. Baker (Climate Dynamics, 2011)

Evaluation of the use of recN sequence analysis in the phylogeny of the genus Amycolatopsis - Gareth J. Everest; Andrew E. Cook; Bronwyn M. Kirby; Paul R. Meyers (Antonie van Leeuwenhoek, 2011)

Transcriptome sequencing of an ecologically important graminivorous sawfly: a resource for marker development - N. Cook; N. Aziz; P. E. Hedley; J. Morris; L. Milne; A. J. Karley; S. F. Hubbard; J. R. Russell (Conservation Genetics Resources, 2011)

Tobacco withdrawal components and their relations with cessation success - Megan E. Piper; Tanya R. Schlam; Jessica W. Cook; Megan A. Sheffer; Stevens S. Smith; Wei-Yin Loh; Daniel M. Bolt; Su-Young Kim; Jesse T. Kaye; Kathryn R. Hefner; Timothy B. Baker (Psychopharmacology, 2011)

Broad‐scale latitudinal patterns of genetic diversity among native European and introduced house sparrow ( Passer domesticus ) populations - A. W. SCHREY; M. GRISPO; M. AWAD; M. B. COOK; E. D. McCOY; H. R. MUSHINSKY; T. ALBAYRAK; S. BENSCH; T. BURKE; L. K. BUTLER; R. DOR; H. B. FOKIDIS; et al. (Molecular Ecology, 2011)
Introduced species offer unique opportunities to study evolution in new environments, and some provide opportunities for understanding the mechanisms underlying macroecological patterns. We sought to determine how introduction history impacted genetic diversity and differentiation of the house sparrow ( Passer domesticus ), one of the most broadly distributed bird species. We screened eight microsatellite loci in 316 individuals from 16 locations in the native and introduced ranges. Significant population structure occurred between native than introduced house sparrows. Introduced house sparrows were distinguished into one North American group and a highly differentiated Kenyan group. Genetic differentiation estimates identified a high magnitude of differentiation between Kenya and all other populations, but demonstrated that European and North American samples were differentiated too. Our results support previous claims that introduced North American populations likely had few source populations, and indicate house sparrows established populations after introduction. Genetic diversity also differed among native, introduced North American, and Kenyan populations with Kenyan birds being least diverse. In some cases, house sparrow populations appeared to maintain or recover genetic diversity relatively rapidly after range expansion (

Wind speed and wind-associated leaf injury affect severity of citrus canker on Swingle citrumelo - C. H. Bock; James H. Graham; Tim R. Gottwald; Amanda Z. Cook; Paul E. Parker (European Journal of Plant Pathology, 2010)

Genetic variation in sex-steroid receptors and synthesizing enzymes and colorectal cancer risk in women - Jennifer Lin; Robert Y. L. Zee; Kuang-Yu Liu; Shumin M. Zhang; I-Min Lee; JoAnn E. Manson; Edward Giovannucci; Julie E. Buring; Nancy R. Cook (Cancer Causes & Control, 2010)

The Horsfall-Barratt scale and severity estimates of citrus canker - C. H. Bock; T. R. Gottwald; P. E. Parker; A. Z. Cook; F. Ferrandino; S. Parnell; F. van den Bosch (European Journal of Plant Pathology, 2009)

Physical activity, adiposity, and risk of endometrial cancer - Molly B. Conroy; Jacob R. Sattelmair; Nancy R. Cook; JoAnn E. Manson; Julie E. Buring; I-Min Lee (Cancer Causes & Control, 2009)

Cryptic seedling herbivory by nocturnal introduced generalists impacts survival, performance of native and exotic plants - Sharon Y. Strauss; Maureen L. Stanton; Nancy C. Emery; Carrie A. Bradley; Alexandra Carleton; Dylan R. Dittrich-Reed; Olivia A. Ervin; Levi N. Gray; Andrew M. Hamilton; Jennifer Harrington Rogge; Skye D. Harper; Kimberley Cook Law; et al. (Ecology, 2009)
Although much of the theory on the success of invasive species has been geared at escape from specialist enemies, the impact of introduced generalist invertebrate herbivores on both native and introduced plant species has been underappreciated. The role of nocturnal invertebrate herbivores in structuring plant communities has been examined extensively in Europe, but less so in North America. Many nocturnal generalists (slugs, snails, and earwigs) have been introduced to North America, and 96% of herbivores found during a night census at our California Central Valley site were introduced generalists. We explored the role of these herbivores in the distribution, survivorship, and growth of 12 native and introduced plant species from six families. We predicted that introduced species sharing an evolutionary history with these generalists might be less vulnerable than native plant species. We quantified plant and herbivore abundances within our heterogeneous site and also established herbivore removal experiments in 160 plots spanning the gamut of microhabitats. As 18 collaborators, we checked 2000 seedling sites every day for three weeks to assess nocturnal seedling predation. Laboratory feeding trials allowed us to quantify the palatability of plant species to the two dominant nocturnal herbivores at the site (slugs and earwigs) and allowed us to account for herbivore microhabitat preferences when analyzing attack rates on seedlings. The relationship between local slug abundance and percent cover of five common plant taxa at the field site was significantly negatively associated with the mean palatability of these taxa to slugs in laboratory trials. Moreover, seedling mortality of 12 species in open‐field plots was positively correlated with mean palatability of these taxa to both slugs and earwigs in laboratory trials. Counter to expectations, seedlings of native species were neither more vulnerable nor more palatable to nocturnal generalists than those of introduced species. Growth comparison of plants within and outside herbivore exclosures also revealed no differences between native and introduced plant species, despite large impacts of herbivores on growth. Cryptic nocturnal predation on seedlings was common and had large effects on plant establishment at our site. Without intensive monitoring, such predation could easily be misconstrued as poor seedling emergence.

Resolving relationships in some African fungus-growing termites (Termitidae, Macrotermitinae) using molecular phylogeny, morphology, and field parameters - J. P. E. C. Darlington; R. B. Benson; C. E. Cook; G. Walker (Insectes Sociaux, 2008)

A cross‐taxa phenological dataset from Mohonk Lake, NY and its relationship to climate - Benjamin I. Cook; Edward R. Cook; Paul C. Huth; John E. Thompson; Anna Forster; Daniel Smiley (International Journal of Climatology, 2008)
We present a detailed analysis of a rare cross‐taxa native species phenology dataset (plant flowering, insect first sighting, and amphibian first sighting) from Mohonk Lake, NY. This dataset is highly unusual in North America for its longevity of record, consistency of methodology and location, diversity of species available, and availability of local daily meteorological data. For each phenology series, we examined the flowering and first sighting Julian calendar dates for the existence of temporal trends. Only one of the five animal species (katydid) showed any evidence for a significant trend in first sighting. In contrast, the plant species showed a rich mixture of temporal trends in flowering that could be divided into four classes: woody plant–no trend, woody plant–negative trend, herbaceous plant–negative trend, and herbaceous plant–positive trend. Many of the trends were found to be statistically significant and robust to the method of trend estimation. The data within each of the four plant classes were also pooled as anomalies to provide more complete temporal coverage for tests of trend robustness. The results were strongly consistent with the trends of the individual species within each class and highly significant statistically. We next correlated the flowering and first sighting dates against growing degree‐day (GDD) summations for each day of the year to measure the sensitivity of each species to this common form of climatic forcing on phenology. All species showed a significant sensitivity to GDD summations, with peak correlations falling on or near the varying median flowering or first sighting dates. These results were robust whether the GDD analyses were conducted over the complete set of observations for each species (beginning on or after 1928) or over a latter period with a more serially complete set of cross‐taxa observations (1970–2002). The GDD correlations indicate significant climate sensitivity in all species, but the different magnitudes of correlation and timing of maximum correlation imply that plant and animal responses to climate changes in the future will not be homogeneous for the tested species at Mohonk Lake. Copyright © 2007 Royal Meteorological Society

Brian MacMahon (1923–2007): founder of modern epidemiology - D. Trichopoulos; P. Cole; E. F. Cook; M. Feinleib; R. Hoover; C.-C. Hsieh; D. Hunter; R. Monson; N. Mueller; M. Rahu; E. Rimm; K. Rothman; et al. (Cancer Causes & Control, 2008)

Len Muscatine (1932–2007) and his contributions to the understanding of algal-invertebrate endosymbiosis - O. Hoegh-Guldberg; G. Muller-Parker; C. B. Cook; R. D. Gates; E. Gladfelter; R. K. Trench; V. M. Weis (Coral Reefs, 2007)

CO 2 balance of boreal, temperate, and tropical forests derived from a global database - S. LUYSSAERT; I. INGLIMA; M. JUNG; A. D. RICHARDSON; M. REICHSTEIN; D. PAPALE; S. L. PIAO; E. ‐D. SCHULZE; L. WINGATE; G. MATTEUCCI; L. ARAGAO; M. AUBINET; et al. (Global Change Biology, 2007)
Terrestrial ecosystems sequester 2.1 Pg of atmospheric carbon annually. A large amount of the terrestrial sink is realized by forests. However, considerable uncertainties remain regarding the fate of this carbon over both short and long timescales. Relevant data to address these uncertainties are being collected at many sites around the world, but syntheses of these data are still sparse. To facilitate future synthesis activities, we have assembled a comprehensive global database for forest ecosystems, which includes carbon budget variables (fluxes and stocks), ecosystem traits (e.g. leaf area index, age), as well as ancillary site information such as management regime, climate, and soil characteristics. This publicly available database can be used to quantify global, regional or biome‐specific carbon budgets; to re‐examine established relationships; to test emerging hypotheses about ecosystem functioning [e.g. a constant net ecosystem production (NEP) to gross primary production (GPP) ratio]; and as benchmarks for model evaluations. In this paper, we present the first analysis of this database. We discuss the climatic influences on GPP, net primary production (NPP) and NEP and present the CO 2 balances for boreal, temperate, and tropical forest biomes based on micrometeorological, ecophysiological, and biometric flux and inventory estimates. Globally, GPP of forests benefited from higher temperatures and precipitation whereas NPP saturated above either a threshold of 1500 mm precipitation or a mean annual temperature of 10 °C. The global pattern in NEP was insensitive to climate and is hypothesized to be mainly determined by nonclimatic conditions such as successional stage, management, site history, and site disturbance. In all biomes, closing the CO 2 balance required the introduction of substantial biome‐specific closure terms. Nonclosure was taken as an indication that respiratory processes, advection, and non‐CO 2 carbon fluxes are not presently being adequately accounted for.

Alkaloid Profiles, Concentration, and Pools in Velvet Lupine (Lupinus leucophyllus) Over the Growing Season - Stephen T. Lee; Michael H. Ralphs; Kip E. Panter; Daniel Cook; Dale R. Gardner (Journal of Chemical Ecology, 2007)

Dietary intakes of fruit, vegetables, and fiber, and risk of colorectal cancer in a prospective cohort of women (United States) - Jennifer Lin; Shumin M. Zhang; Nancy R. Cook; Kathryn M. Rexrode; Simin Liu; JoAnn E. Manson; I-Min Lee; Julie E. Buring (Cancer Causes & Control, 2005)

Development of a micro-sward technique for determining intake characteristics of perennial ryegrass varieties - R. J. Orr; K. L. Young; J. E. Cook; R. A. Champion (Euphytica, 2005)

High-quality RNA, cDNA, and derived EST libraries from grapevine (Vitis vinifera L.) - A. B. Iandolino; F. Goes da Silva; H. Lim; H. Choi; L. E. Williams; D. R. Cook (Plant Molecular Biology Reporter, 2004)

Body Mass Index and Risk of Colorectal Cancer in Women (United States) - Jennifer Lin; Shumin M. Zhang; Nancy R. Cook; Kathryn M. Rexrode; I-Min Lee; Julie E. Buring (Cancer Causes & Control, 2004)

West Nile virus: pending crisis for greater sage‐grouse - David E. Naugle; Cameron L. Aldridge; Brett L. Walker; Todd E. Cornish; Brendan J. Moynahan; Matt J. Holloran; Kimberly Brown; Gregory D. Johnson; Edward T. Schmidtmann; Richard T. Mayer; Cecilia Y. Kato; Marc R. Matchett; et al. (Ecology Letters, 2004)
Scientists have feared that emerging infectious diseases could complicate efforts to conserve rare and endangered species, but quantifying impacts has proven difficult until now. We report unexpected impacts of West Nile virus (WNv) on radio‐marked greater sage‐grouse ( Centrocercus urophasianus ), a species that has declined 45–80% and is endangered in Canada and under current consideration for federal listing in the US. We show that WNv reduced late‐summer survival an average of 25% in four radio‐marked populations in the western US and Canada. Serum from 112 sage‐grouse collected after the outbreak show that none had antibodies, suggesting that they lack resistance. The spread of WNv represents a significant new stressor on sage‐grouse and probably other at‐risk species. While managing habitat might lessen its impact on sage‐grouse populations, WNv has left wildlife and public health officials scrambling to address surface water and vector control issues in western North America.

AZT inhibits Visna/maedi virus -induced apoptosis - V. Bellet; R. Duval; S. Delebasse; J. Cook-Moreau; C. Bosgiraud (Archives of Virology, 2004)

The severe combined immunodeficient (SCID) mouse model of human immunodeficiency virus encephalitis: Deficits in cognitive function - William C Griffin; Lawrence D Middaugh; Jennifer E Cook; William R Tyor (Journal of NeuroVirology, 2004)

Influence of pasture management (nitrogen and lime addition and insecticide treatment) on soil organisms and pasture root system dynamics in the field - L. A. Dawson; S. J. Grayston; P. J. Murray; R. Cook; A. C. Gange; J. M. Ross; S. M. Pratt; E. I. Duff; A. Treonis (Plant and Soil, 2003)

Deep Natural Gas Resources - T. S. Dyman; R. E. Wyman; V. A. Kuuskraa; M. D. Lewan; T. A. Cook (Natural Resources Research, 2003)

Estrogen–progestin replacement therapy and breast cancer risk: the Women's Health Study (United States) - Juliet V. Porch; I-Min Lee; Nancy R. Cook; Kathryn M. Rexrode; Julie E. Buring (Cancer Causes & Control, 2002)

A Riparian Wildlife Habitat Evaluation Scheme Developed Using GIS - DIANE L. SZAFONI; LOUIS R. IVERSON; SHARON E. BAUM; ELIZABETH A. COOK (Environmental Management, 2001)

The climatic response of Phyllocladus aspleniifolius (Labill.) Hook. f in Tasmania - K. J. Allen; E. R. Cook; R. J. Francey; K. Michael (Journal of Biogeography, 2001)
Aim To examine the response of ring widths of Phyllocladus aspleniifolius to maximum and minimum temperatures and to a zonal index (ZI). Location Tasmania, Australia. Methods Between two and four increment cores were obtained from approximately 20 trees at each of 16 sites of P. aspleniifolius across Tasmania. Four regions were defined and temperature data for climate stations from each of these regions were transformed into dimensionless time series appropriate for each region. The ZI was constructed from Melbourne and Hobart mean sea level pressure (MSLP). Correlations were calculated between climate data and ring widths over most of the 20th century. Data were then segregated into two subperiods to assess whether or not temporal changes in ring width response have occurred over the 20th century. Results The dominant feature of the correlation functions was a negative correlation with temperatures of the previous growing season. Correlation between the ZI and ring width is most significant, and positive, in November and March of the previous growing season. Differences in the shape of the correlation functions, and their strength is apparent over the course of the century. In general, correlations have become weaker and less consistent among the 16 sites for the latter part of the century. Temperatures have generally increased during the 1900s over which time period correlations have been calculated. Main conclusions The temporally changing climatic response in ring widths is consistent with a hypothesis of competition for resources between different parts of a plant. A nonlinear response to climate over a short‐time period violates one of the basic assumptions of dendroclimatology, therefore suggesting further investigation of both the physiology of trees used for dendroclimatological purposes and the statistical methods used for climatic reconstruction.

Physical activity and breast cancer risk: the Women's Health Study (United States) - I-Min Lee; Kathryn M. Rexrode; Nancy R. Cook; Charles H. Hennekens; Julie E. Buring (Cancer Causes & Control, 2001)

Trans-Tasman Sea climate variability since ad 1740 inferred from middle to high latitude tree-ring data - R. D'Arrigo; E. Cook; R. Villalba; B. Buckley; J. Salinger; J. Palmer; K. Allen (Climate Dynamics, 2000)

Effects of beta-carotene supplementation on cancer incidence by baseline characteristics in the Physicians' Health Study (United States) - Nancy R. Cook; I-Min Lee; JoAnn E. Manson; Julie E. Buring; Charles H. Hennekens (Cancer Causes & Control, 2000)

Warm-season temperatures since 1600 BC reconstructed from Tasmanian tree rings and their relationship to large-scale sea surface temperature anomalies - E. R. Cook; B. M. Buckley; R. D. D'Arrigo; M. J. Peterson (Climate Dynamics, 2000)

Bay‐scale population structure in coastal Atlantic cod in Labrador and Newfoundland, Canada - D. E. Ruzzante; J. S. Wroblewski; C. T. Taggart; R. K. Smedbol; D. Cook; S. V. Goddaard (Journal of Fish Biology, 2000)
Polymorphisms at five microsatellite DNA loci provide evidence that Atlantic cod Gadus morhua inhabiting Gilbert Bay, Labrador are genetically distinguishable from offshore cod on the north‐east Newfoundland shelf and from inshore cod in Trinity Bay, Newfoundland. Antifreeze activity in the blood suggests that Gilbert Bay cod overwinter within the Bay. Gilbert Bay cod are also smaller (weight and length) for their age and consequently less fecund for their age, than cod elsewhere within the northern cod complex. The productivity and recruitment potential of coastal cod off Labrador may thus be much lower than that of offshore northern cod or of inshore cod farther south, implying that a more conservative management strategy may be required for cod from coastal Labrador than traditionally practised for northern cod inhabiting less harsh environments. Relatively high F ST and R ST measures of population structure suggest that important barriers to gene flow exist among five components that include two inshore (Gilbert and Trinity Bay) and three offshore cod aggregations on the north‐east Newfoundland Shelf and the Grand Bank. D A and D SW estimates of genetic distance that involve Gilbert Bay cod are approximately three‐ and 10–fold larger, respectively, than estimates not involving Gilbert Bay cod. The differences between inshore cod from Gilbert Bay and Trinity Bay raise the possibility that other genetically distinguishable coastal populations may exist, or may have existed prior to the northern cod fishery collapse. Harvesting strategies for northern cod should recognize the existence of genetic diversity between inshore and offshore components as well as among coastal components.

Hair product use and the risk of breast cancer in young women - Linda S. Cook; Kathleen E. Malone; Janet R. Daling; Lynda F. Voigt; Noel S. Weiss (Cancer Causes & Control, 1999)

Identification of three genes expressed primarily during development in Physarum polycephalum - J. Bailey; L. J. Cook; R. Kilmer-Barber; E. Swanson; L. Solnica-Krezel; K. Lohman; W. F. Dove; J. Dee; R. W. Anderson (Archives of Microbiology, 1999)

Abstracts of papers presented at an international workshop on management of soilborne pathogens sponsored by the United States-Israel binational agricultural research and development fund (bard) - R. J. Cook; J. Katan; I. Chet; J. Katan; R. Rodriguez-Kabana; C. R. Taylor; J. W. Kloepper; M. M. Satour; G. L. Lazarovits; K. L. Conn; M. Tenuta; G. Kritzman; et al. (Phytoparasitica, 1998)

Comparison of Ceralure and Trimedlure Controlled-Release Formulations for Male Mediterranean Fruit Flies in C&C Traps - J. D. Warthen; R. T. Cunningham; B. A. Leonhardt; J. M. Cook; J. W. Avery; E. M. Harte (Journal of Chemical Ecology, 1998)

Tree-ring records from New Zealand: long-term context for recent warming trend - R. D. D'Arrigo; E. R. Cook; M. J. Salinger; J. Palmer; P. J. Krusic; B. M. Buckley; R. Villalba (Climate Dynamics, 1998)

Sea-level pressure variability around Antarctica since A.D. 1750 inferred from subantarctic tree-ring records - R. Villalba; E. R. Cook; R. D. D'Arrigo; G. C. Jacoby; P. D. Jones; M. J. Salinger; J. Palmer (Climate Dynamics, 1997)

A CHANGING TEMPERATURE RESPONSE WITH ELEVATION FOR LAGAROSTROBOS FRANKLINII IN TASMANIA, AUSTRALIA - B. M. BUCKLEY; E. R. COOK; M. J. PETERSON; M. BARBETTI (Climatic Change, 1997)

Improved Controlled-Release Formulations for a New Trap Design for Male Mediterranean Fruit Flies: The C&C Trap - J. D. Warthen; R. T. Cunningham; B. A. Leonhardt; J. M. Cook; J. W. Avery; E. M. Harte (Journal of Chemical Ecology, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

A recombinant fowlpox virus that expresses the VP2 antigen of infectious bursal disease virus induces protection against mortality caused by the virus - C. D. Bayliss; R. W. Peters; Jane K. A. Cook; R. L. Reece; K. Howes; M. M. Binns; M. E. G. Boursnell (Archives of Virology, 1991)

Detection and prevalence of serotypes of feline syncytial spumaviruses - R. L. P. Flower; G. E. Wilcox; R. D. Cook; T. M. Ellis (Archives of Virology, 1985)

Sectional notes - W. B. Ward; Allan Purdy; Marx Koeiinke; H. J. Evans; Harrold Mattson; E. B. Tussing; Harold T. Cook; M. R. Harris; R. E. Goodwin; W. N. Keenan (American Journal of Potato Research, 1947)